Numerical Modeling of Anisotropic Elastic-Wave Sensitivity Propagation for Optimal Design of Time-Lapse Seismic Surveys (Communications in Computational Physics, 2020)
Reliable subsurface time-lapse seismic monitoring is crucial for many geophysical applications, such as enhanced geothermal system characterization, geologiccarbon utilization and storage, and conventional and unconventional oil/gas reservoircharacterization, etc. We develop an elastic-wave sensitivity propagation method foroptimal design of cost-effective time-lapse seismic surveys considering the fact thatmost of subsurface geologic layers and fractured reservoirs are anisotropic insteadof isotropic. For anisotropic media, we define monitoring criteria using qP- and qS-wave sensitivity energies after decomposing qP- and qS-wave components from thetotal elastic-wave sensitivity wavefield using a hybrid time- and frequency-domainapproach. Geophones should therefore be placed at locations with significant qP- and qS-wave sensitivity energies for cost-effective time-lapse seismic monitoring in ananisotropic geology setting. Our numerical modeling results for a modified anisotropicHess model demonstrate that, compared with the isotropic case, subsurface anisotropychanges the spatial distributions of elastic-wave sensitivity energies. Consequently,it is necessary to consider subsurface anisotropies when designing the spatial distribution of geophones for cost-effective time-lapse seismic monitoring. This findingsuggests that it is essential to use our new anisotropic elastic-wave sensitivity modeling method for optimal design of time-lapse seismic surveys to reliably monitor thechanges in subsurface reservoirs, fracture zones or target monitoring regions.
Keywords: Anisotropy; elastic-wave sensitivity; time-lapse seismic monitoring.